ANALISIS INTEGRASI PASAR KOMODITAS CABAI RAWIT DI PROVINSI GORONTALO - Yuliana Bakari; Echan Adam; Sirin Aditia (Universitas Sebelas Maret, 2024)
This study aims to analyze the vertical market integration of cayenne pepper in Gorontalo Province. The sampling method is based on the availability of cayenne pepper price data over a period of 4 years (2017 to 2020). The type of data source in this study is secondary data, namely data on the price of cayenne pepper at the producer, wholesaler, and consumer levels. The analytical method used in this study is quantitative. The quantitative method uses cointegration analysis and ECM (error correction model). The results show that the cayenne pepper market in Gorontalo Province has been integrated iboth i!in the short and long term between farmers and marketing institutions/ wholesalers, marketing institutions/ wholesalers and consumers, and between consumers and farmers. That is, if there is a change in the price of cayenne pepper at the consumer level, it will be transmitted to the level of marketing institutions/wholesalers. And if there is a change in the price of cayenne pepper at the wholesaler level, it will be transmitted to farmers. Then the market between consumers and farmers is integrated based on the model used.